Financial Incentives for Medicaid Beneficiaries With Diabetes: Lessons Learned From HI-PRAISE, an Observational Study and Randomized Controlled Trial. Issue 7 (September 2018) - Fernandes, Ritabelle; Chinn, Chuan C.; Li, Dongmei; Halliday, Timothy; Frankland, Timothy B.; Wang, Christina M. B.; Wang, Zi; Morioka, Misha; Arndt, Robin G.; Ozaki, Rebecca Rude
Purpose: The Hawaii Patient Reward and Incentives to Support Empowerment (HI-PRAISE) project examined the impact of financial incentives on Medicaid beneficiaries with diabetes. Design: Observational pre–post study and randomized controlled trial (RCT). Setting: Federally qualified health centers (FQHCs) and Hawaii Kaiser Permanente. Participants: The observational study included 2003 Medicaid beneficiaries with diabetes from FQHCs. The RCT included 320 participants from Kaiser Permanente. Intervention: Participants could earn up to 320/year of financial incentives for a minimum of 1 year. Measures: (1) Clinical outcomes of change in hemoglobin A1c (HbA1c ), blood pressure, and cholesterol; (2) compliance with American Diabetes Association (ADA) standards of diabetes care; and (3) cost effectiveness. Analysis: Generalized estimating equation models were used to assess differences in clinical outcomes. General linear models were utilized to estimate the medical costs per patient/day. Results: Changes in clinical outcomes in the observational study were statistically significant. Mean HbA1c decreased from 8.56% to 8.24% ( P < .0001) and low-density lipoprotein decreased from 106.17 mg/dL to 98.55 mg/dL ( P < .0001). No significant differences were found between groups in the RCT. Improved ADA compliance was observed. No reduction in total health cost during the project period was demonstrated. Conclusion: The HI-PRAISE found no conclusive evidence that financial incentives had beneficial effect on diabetes clinical outcomes or cost saving measures.